Development and evaluation of clozapine intranasal mucoadhesive in situ gels for brain targeting - Ravikrishna, Velupula; Krishnaveni, Janapareddi (Journal of Drug Delivery and Therapeutics, 2019)
Blood brain barrier, poor solubility and low bioavailability (<27%) due to hepatic metabolism are major constraints of clozapine (CZP) oral tablets for their clinical application in the treatment of psychosis. Therefore, the study aims to develop pluronic based thermosensitive mucoadhesive in situ gel of clozapine for brain targeting through intranasal olfactory pathway. The objective of the present study was to develop an aqueous and oil based thermosensitive mucoadhesive in situ gel of clozapine for intranasal delivery and to evaluate the gels for in vitro characterization and ex vivo permeation in comparison to drug solution. The aqueous and oil based in situ gel systems were developed by cold method using water and oleic acid as solvents respectively. Combination of Pluronic F-127 and F-68 (20:2) were used as thermosensitive gelling agents. Labrasol and Transcutol P at 1:1 ratio were employed as co solvents for the solubilisation of drug. The prepared in situ gels were evaluated for clarity, gelation temperature (Tsol-gel), gelation time (GT), gel strength (GS), pH, viscosity, mucoadhesive strength and ex vivo drug permeation studies. The effect of mucoadhesive agents like Chitosan, Sodium-β- glycerophosphate and Polyox WSR303 on gelation temperature (Tsol-gel) and drug permeation was also evaluated. The optimized aqueous in situ gel with 0.5% chitosan (Fa15) showed viscosity 554.66±8.73cP at 31oC; mucoadhesive strength 5114.91±107.37dynes/cm2, gelation temperature (Tsol-gel) 29.6±1.7 oC and gelation time (GT) 69±5 sec. The flux was found to be 243.46 µg/cm2/hr which was significantly high (p<0.0001) compared to drug solution and the enhancement ratio(ER) was found to be 2.28 folds to the drug solution whereas the oil gel showed flux of 190.34 µg/cm2/hr and enhancement ratio was found to be1.64 folds to the drug solution. The results indicated that the hydrogels are potential carriers than oil gels for delivery of clozapine via intranasal route. Keywords: Clozapine, in situ gels, nasal drug delivery, olfactory pathway, brain targeting, psychosis